On groups with a small number of classes of conjugate noncomplemented subgroups - Bilotskii, N. N.; Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We give a description of finite nonprimary groups that contain at most two classes of conjugate noncomplemented subgroups.